Associations of plant fitness, leaf chemistry, and damage suggest selection mosaic in plant-herbivore interactions. - Muola, A; Mutikainen, P; Lilley, M; Laukkanen, L; Salminen, J; Leimu, R (2010)
The geographic mosaic theory of coevolution states that variation in species interactions forms the raw material for coevolutionary processes, which take place over large geographic scales. One key assumption underlying the process of coevolution in plant-herbivore interactions is that herbivores exert selection on their host plants and that this selection varies among plant populations. We examined spatial variation in the existence and strength of phenotypic selection on host plant resistance exerted by specialist herbivores in 17 archipelago populations of the perennial herb Vincetoxicum hirundinaria (Asclepiadaceae). In these highly fragmented populations, V. hirundinaria is consumed by the larvae of two specialist herbivores: the folivorous moth Abrostola asclepiadis and the seed predator Euphranta connexa. Selection imposed on host plants by these herbivores was examined by analyzing the associations between levels of herbivory, plant fitness, and contents of a number of leaf chemicals reflecting plant resistance to and quality for the herbivores. We found extensive spatial variation in the levels of herbivory and in plant fitness. More importantly, the impact of both leaf herbivory and seed predation on plant fitness varied among plant populations, indicating spatial variation in phenotypic selection. In addition, leaf chemistry varied widely among plant populations, reflecting spatial variation in plant quality as food for the herbivores. However, leaf compounds influenced folivory similarly in all the studied plant populations, and interestingly, some of the compounds were associated with the intensity of seed predation. Finally, some of the leaf compounds were associated with plant fitness, and the strength and direction of these associations varied among plant populations. The observed spatial variation in the strength of the interactions between V. hirundinaria and its specialist herbivores suggests a geographic selection mosaic. Because the occurrence and strength of spatial variation varied between the two specialist herbivores, our results highlight the importance of considering multiple enemies when trying to understand evolution of interactions between plants and their herbivores.